THE PERFORMANCE OF CAPITAL STRUCTURE ON SHARIAH-COMPLIANT FIRMS IN MALAYSIA - Isa , Aflah; Romli , Nurulashikin; Khaidzir , Halimatun Saadiah; Haris , Sharazad; Jaini, Azila (International Journal of Accounting, Finance and Business, 2024)
This research aims to provide information on the capital structure performance of Malaysian shariah-compliant technology companies listed on Bursa Malaysia. From 2010 through 2020, these studies used Eviews software to analyze secondary data. According to the random effect results, profitability, expansion potential, firm size, tangibility, business risk, and GDP growth are the determinants that significantly impact leverage for trading firms in the Malaysian market. Furthermore, researchers expected that shariah-compliant enterprises' power positively correlates with profitability, business size, tangibility, and GDP growth. However, there is no correlation between growth prospects and company risk when it comes to the power of Sharia-compliant businesses.